Information-seeking behaviors and barriers to the incorporation of scientific evidence into clinical practice: A survey with Brazilian dentists. - Branca Heloisa Oliveira; Izabel Monteiro D Hyppolito; Zilson Malheiros; Bernal Stewart; Claudio Mendes Pannuti (PLoS ONE, 2021)
The aim of this online cross-sectional study is to identify the sources of scientific information used by Brazilian dentists in clinical decision-making and the barriers that they perceive as important to the incorporation of scientific evidence into clinical practice. A pretested questionnaire created in Google Forms which was made available to participants through links sent by e-mail or shared on Facebook® and Instagram® was used to collect the data between October 2018 and May 2019. Only dentists who were involved in direct or indirect care of patients (i.e. clinicians who performed dental procedures or dental educators who participated in the clinical training of graduate or postgraduate dental students) were asked to complete the questionnaire. The sample was comprised of 528 dentists (the response rate from the alumni database was 6.9%); their mean age was 45.2 years (±12.5) and 30.9% had an academic position. The majority were women (68.0%) and lived in Southern or Southeastern Brazil (96.0%). The sources of scientific information more frequently used by them in clinical decision-making were clinical guidelines (65.1%; 95% CI: 60.9, 69.2), scientific articles (56.8%; 95%CI: 52.5, 61.1) and bibliographic databases (48.3%; 95% CI: 43.9, 52.6). The information resource less frequently used was social media. The most important barriers to the clinical use of scientific evidence were: difficulty in determining whether scientific contents found on the Internet were reliable or not (41.8%; 95% CI: 37.6, 46.2), high cost of access to scientific papers (37.7%; 95% CI: 33.5, 41.9), and lack of time for reading scientific articles (32.4%; 95% CI: 28.4, 36.6). Although Brazilian dentists show a positive attitude towards obtaining scientific evidence from reliable sources, there still remain important barriers to the translation of evidence into practice. This can have significant implications for quality of care and should be further investigated.